Vermin writing. (2nd July 2020) - Nagai, Kaori
ABSTRACT: This article coins the term 'vermin writing' to refer to the ways in which non-human animals emerge as 'vermin' in human documents and leave their traces on them. It discusses examples of vermin writing in nineteenth-century maritime history, with special attention to rats. By looking at a range of maritime documents, such as logbooks, surveys of ships' stores, insurance court cases, and ships' magazines, it identifies common features of vermin writing and explores how 'verminous' animals were represented and treated on board ship. Despite their ubiquity, 'vermin' were sparingly recorded in official documents, except when they were implicated in losses and damage. On the other hand, private documents of ships' crews and passengers contain many moments of vermin writing, revealing how interspecific the shipborne community once was.